(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The total phenol and flavanoids were measured in ethanol, ethyl acetate and water extracts of unripe pericarp of fruits of Annona reticulata Linn. Ethanol extract showed high phenol and flavonoid contents. The ethanolic crude extract is also screened for its free radical scavenging properties using various in vitro assays like DPPH radical scavenging assay, hydroxyl radical scavenging assay, nitric oxide radical scavenging assay, hydrogen peroxide radical scavenging assay and superoxide radical scavenging assay. Ethanol extract exhibited the strongest antioxidant capacity in all used assays and its effect is comparable to the synthetic antioxidant Ascorbate. The total phenol content (TPC) showed a very strong positive significant (P